Developmental Implications of Youth Sport Participation on Physical Activity and Sport Participation in Young Adulthood - Flournoy, Fletcher J (East Carolina University, 2017)
This study sought to address a point of controversy within youth sports: whether young athletes should specialize early (e.g., Ericsson, Krampe & Tesch-Römer, 1993) or if it is favorable to follow the path of early diversification and multiple sport participation (e.g., Côté, Leder and Hackfort, 2009). Based on a sample of students (N=109) from East Carolina University who were former athletes, the present study investigated whether former youth sport specializers and former multi-sport athletes differed on their reported experiences in sport for Basic Need Satisfaction (BNS), Motivation Type (MT), and Athlete Burnout (ABQ). The results from this sample reveal that there were no significant differences between the two groups based on BNS, MT, or ABQ to support the study hypotheses. However, results revealed that study participants who reported participating on a "travel team" were significantly less likely to report "a reduced sense of accomplishment" (a subscale of the ABQ) when compared to participants who reported no travel team participation. Correlation analyses demonstrated a negative relationship between reduced sense of accomplishment and basic needs satisfaction. Specifically, participants who reported high levels of reduced sense of accomplishment were more likely to report lower levels of basic need satisfaction at a significant rate. Independent samples t-tests revealed that study participants who ceased participating in sports as adults also reported significantly higher overall athlete burnout and devaluation of sport when compared to those who continued in sports, regardless of specialization status. Participation in a single or multiple youth sports had no relationship to sport participation in young adulthood. For this sample of college students, factors related to athlete burnout played a significant role in continued participation in young adulthood. Future research should utilize a longitudinal design with current youth athletes as opposed to retrospective research with former youth athletes.
Keywords: youth sport specialization; basic need satisfaction; motivation type; multi-sport athlete; Sports for children--Psychological aspects; Sports for children--Physiological aspects.; Burn out (Psychology)